2022
DOI: 10.1002/cctc.202201008
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Molybdenum Imido Alkylidene N‐Heterocyclic Carbene Complexes Confined in Mesoporous Silica: Tuning Transition States Towards Z‐Selective Ring‐Opening Cross‐Metathesis

Abstract: We recently reported a method for selective macro(mono)cyclization of dienes utilizing catalysts confined inside the pores of mesoporous silica, which we believe occurs due to suppression of oligomerization due to pore size. We hypothesized, however, that the system of cationic molybdenum imido alkylidene N-heterocyclic carbene (NHC) catalysts immobilized selectively inside the mesopores of silica materials could address much more subtle selectivity differences, such as E/Z selectivity in ring-opening/cross-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Macrocyclization and Z-selectivity are highest with the smallest pores. The results presented here are in line with those obtained previously both in the macrocyclization and ring-opening crossmetathesis (ROCM) [6] with cationic molybdenum imido alkylidene NHC complexes under confinement and illustrate the generality of the confinement approach outlined here.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Macrocyclization and Z-selectivity are highest with the smallest pores. The results presented here are in line with those obtained previously both in the macrocyclization and ring-opening crossmetathesis (ROCM) [6] with cationic molybdenum imido alkylidene NHC complexes under confinement and illustrate the generality of the confinement approach outlined here.…”
Section: Discussionsupporting
confidence: 90%
“…Even though the specific surface area of OMS 33Å is more than twice as large as that of OMS 68Å , the catalyst loadings on OMS 68Å are significantly larger. This effect may be rationalized by increasing diffusion limitations of W1 and W2 into the mesopores with decreasing pore sizes [6,9] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18][19] Such pore-selective immobilization is an indispensable prerequisite since even small amounts of catalysts located outside the pores substantially obliterate connement effects. 20 One important nding was that the transition states of an organometallic catalyst can be tuned by locating the catalyst close to the surface, thereby generating steric constraints as non-covalent interactions that can be used to, e.g., enhance the Z-selectivity both in the macrocyclization of dienes 19 and in ring-opening cross metathesis reactions 21 that otherwise requires a careful ligand design. 22 Equally important, we found that the pore diameter as such plays a pivotal role.…”
Section: Introductionmentioning
confidence: 99%